Summer Bridge Programs for First-Generation Students in the Christian College Context: Strengths and Challenges - Morton, Brenda (Christian higher education, 2023)
Universities nationwide have sought ways to support the retention of students on their campuses, particularly first-generation students. One such method is through summer bridge programs designed to offer academic and social support to new incoming students in the months before their first year begins. Christian institutions’ faith-based mission statements are integral to developing programming to support first-generation students, as the cultural habitus that emerges from the school’s Christian identity creates a unique cultural landscape that first-generation students navigate. This study is a phenomenological analysis of the experiences of six first-generation college students (FGCS) enrolled in a pilot bridge program on a Christian campus in the Pacific Northwest. The program was created to support the unique needs of FGCS by beginning with a summer orientation and a two-week course and program on campus. Students reported dynamics congruent with the literature on first-generation students, such as academic and financial challenges, mental and personal health issues, and for Latinx students in particular, difficulties navigating dual roles as a student and family member. Unique to our sample is how these challenges are embedded within a Christian college context: Feelings of belonging are inevitably intertwined with this identity, posing unique advantages and disadvantages to their retention. Overall, we argue that the Christian higher education environment is well positioned to enhance the high impact of the bridge programs for their students, although challenges remain.